Cooperative Model Type Group Investigation; An Implementation On Mathematics Learning Straight Line Equation Material - Danaya Leaficha Maweru; Aaltje S. Pangemanan; Anekke Pesik (International Forum of Researchers and Lecturers, 2023)
Learning outcomes refer to the successful attainment of educational objectives by students who actively engage in the process of learning. Nevertheless, it is evident that student learning outcomes remain subpar, hence necessitating the implementation of a learning model aimed at enhancing student learning outcomes. The Group Investigation (GI) Learning Model is an educational approach that has been shown to enhance student learning results. The primary objective of this study was to assess the impact of implementing the Group Investigation (GI) Cooperative learning model and the direct learning model on the learning outcomes of eighth-grade students at SMP N 6 Tondano. Specifically, the study focused on the topic of straight-line equations. The research employed a Quasi-Experimental Design as its chosen methodology. The present study comprised two classes, namely class VIII B as the experimental group and class VIII A as the control group. The sampling methodology employed in this study was Cluster Random Sampling. The methodology employed in this study involves the utilization of written tests for the purpose of data collecting. Based on the findings of the study, the statistical analysis using the t-test yielded a t-value of 2.5709, while the critical t-value (t-table) was determined to be 2.0322. Consequently, the calculated t-value exceeded the critical t-value (t-count > t-table). This implies that the null hypothesis (H0) is rejected in favor of the alternative hypothesis (H1). Based on the findings, it can be inferred that students who were exposed to the Group Investigation (GI) cooperative learning model exhibited superior learning outcomes compared to students who were subjected to the direct learning model. This observation was made specifically in the context of studying straight-line equations among eighth-grade students at SMP Negeri 6 Tondano.